BASMI BASMI: Inovasi Pengelolaan Sampah Berbasis Insinerator Sederhana dan Ember Maggot untuk Desa Babakan Sadeng, Bogor - Edtri, Dewanti Putri; Nurfarinah, Mutiara Azi; Utomo, Eko Cahyo; Atmaja, Muhammad Damas Tri; Pari, Hafly Akeyla; Azaliyah, Siti Hasna; Safitri, Intan; Ningtyas, Nindy Hapsari; Hafizah, Izatul; Pari, Hafly Akeyla Pari (Jurnal Pusat Inovasi Masyarakat, 2025)
The Thematic Community Service Program (KKN-T) is one form of student service to the community through a participatory approach and based on local potential. The 2025 KKN-T program at IPB University was conducted in Babakan Sadeng Village, Leuwisadeng Subdistrict, Bogor Regency, West Java Province, over a period of 40 days, from June 25‒August 4, 2025. The objective of this program is to apply the knowledge and technology gained in the classroom to assist the community in addressing existing issues and support sustainable village development. The main programs implemented cover the fields of environment, food security, community economy, and sustainable education, such as the construction of a simple incinerator for waste management, nutrition and anemia counseling, empowerment of MSMEs through digitalization, and education on environmentally friendly agriculture. The activities were carried out through field observations, discussions with the community and village officials, and a community-based participatory approach. The results of the activity show an increase in public awareness of environmental management and health, as well as the opening of new access to information for local MSMEs. This KKN-T activity not only has a positive impact on the village community but also serves as a contextual learning tool for students in developing social, communication, and leadership skills. This activity is expected to be one of the tangible contributions of IPB students in supporting inclusive and sustainable village development.